Fossil fuel consumption and the environment - Davison, A (Oxford Institute for Energy Studies, 1989)
Energy consumption is intimately bound up with the natural environment. As "green" issues come to the forefront of political debate energy consumption patterns should also come under close scrutiny. This paper describes the major links between commercial energy consumption and the environment, focussing especially on fossil fuels. It then looks at what would be the impact of the growth in world energy demand that is forecast by most "energy experts". The environmental consequences of such growth would in fact be catastrophic, with far- reaching economic consequences. The paper therefore considers ways in which these effects may be avoided. Fuel substitution can offer a partial solution, but it is argued that the easiest, the most effective, and the cheapest solution is energy conservation.